2022
DOI: 10.1186/s13018-022-03007-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with spinal fixation mechanical failure after tumor resection: a systematic review and meta-analysis

Abstract: Background No available meta-analysis has been published that systematically assessed spinal fixation mechanical failure after tumor resection based on largely pooled data. This systematic review and meta-analysis aimed to investigate the spinal fixation failure rate and potential risk factors for hardware failure. Methods Electronic articles published between January 1, 1979, and January 30, 2021, were searched and critically evaluated. The author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…For the size of this bending moment, the present results, in addition to being in the range of the results in previous studies, showed the possibility that relatively large bending moments act on the rod even with an axial compressive load of 700 N alone. In clinical cases, many reports have described rod damage or breakage associated with long fixation, such as spinal stenosis surgery, osteotomy, and circumferential spinal osteotomy [ 11 - 13 ]. Based on our results, high bending stress may act on the rod even in the early postoperative period with limited lumbar flexion and other movements, in patients with such considerable instability, and consideration should be given to the design and selection of rods and screws.…”
Section: Discussionmentioning
confidence: 99%
“…For the size of this bending moment, the present results, in addition to being in the range of the results in previous studies, showed the possibility that relatively large bending moments act on the rod even with an axial compressive load of 700 N alone. In clinical cases, many reports have described rod damage or breakage associated with long fixation, such as spinal stenosis surgery, osteotomy, and circumferential spinal osteotomy [ 11 - 13 ]. Based on our results, high bending stress may act on the rod even in the early postoperative period with limited lumbar flexion and other movements, in patients with such considerable instability, and consideration should be given to the design and selection of rods and screws.…”
Section: Discussionmentioning
confidence: 99%
“…Spinal instrument fractures were most common (4.4%). The mechanical failure of spinal instruments is reported to be 2.0–10% [ 7 , 8 ]. On the other hand, the mechanical failure of a magaprosthesis is reported to be 11.7% [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Spinal instrument fractures were most common (4.4%). The mechanical failure of spinal instruments is reported to be 2.0-10% [7,8]. On the other hand, the mechanical failure of a magaprosthesis is reported to be 11.7% [9].…”
Section: Discussionmentioning
confidence: 99%